Why do banks reward their customers to use their credit cards? - Sumit Agarwal; Sujit Chakravorti; Anna Lunn (Federal Reserve Bank of Chicago, 2010)
Using a unique administrative level dataset from a large and diverse U.S. financial institution, we test the impact of rewards on credit card spending and debt. Specifically, we study the impact of cash-back rewards on individuals before and during their enrollment in the program. We find that with an average cash-back reward of 25, spending and debt increases by 79 and 191 a month, respectively during the first quarter. Furthermore, we find that cardholders who do not use their card prior to the cash-back program increase their spending and debt more than cardholders with debt prior to the cash-back program. In addition, we find that 11 percent of cardholders that did not use their cards in the previous 3 months prior to the cash-back program spent at least 50 in the first month of the program. Finally, we find heterogeneous responses by demographic and credit constraint characteristics.
Keywords: D1; D8; G2; 330; Household Finance; Credit Cards; Consumption; Financial Incentives; Rewards